Development of STEAM-Based Cooperative Learning Model to Increase Student Learning Motivation in Public Elementary Schools in Brebes District, Brebes Regency - Hikmah, Siti Nur; Purwanto, Burhan Eko; Muljani, Sutji (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop and assess the effectiveness of two innovative educational models to enhance student learning motivation and achievement. The first focuses on designing a STEAM-based cooperative learning model to improve students' learning motivation in Public Elementary Schools in Brebes District, Brebes Regency. Through a Research and Development (RD) approach, the study identifies issues such as conventional teacher-centered methods, lack of STEAM integration, unstructured collaboration, and assessment misalignment. Findings indicate a significant improvement in students' motivation, shown by the increase in the experimental class mean score from 52.8000 to 75.0000, supported by statistical analysis (t = 61.562, sig = 2.446 ≥ 0.05), proving the model’s effectiveness. The second part of the study develops a website-based science learning parenting model for broken home students at SMPN 2 Tanjung Brebes. Using the ADD development model, the research addresses the high demand for interactive, accessible, and curriculum-aligned learning media. The website integrates tools like Google Sites, Drive, and Forms, and based on validation and student responses (94% “Very Positive”) as well as improved learning outcomes, the model is deemed effective and feasible for supporting science learning and increasing student involvement.